Effects of High Ambient Temperature and Bypass Protein Supplementation on Performance of Crossbred Lambs - Dahlanuddin Dahlanuddin; C.J. Thwaites; J.V. Nolan (Faculty of Animal Husbandry, University of Mataram, 2016)
The objective of this experiment was to study the effect of dietary supplementation with a source ofbypass protein (cottonseed meal, CSM) on the performance of growing crossbred wethers fed lowdigestibility roughage at high ambient temperature. Sixteen unshorn Border Leicester x Merino lambsaged 6 months and weighing 24.9ï‚±0.37 kg were allocated into a 2x2 factorial design (2 diets and 2ambient temperatures). Each group was fed either wheaten chaff + 2% urea ad libitum or wheaten chaff +1% urea ad libitum + 100g/d cottonseed meal. The results show that respiration rate and rectal temperaturewere significantly affected by ambient temperature (P<0.01), but not by diet. Total dry matter intake wassignificantly higher (P<0.01) at lower temperature than at high temperature, and significantly higher(P=0.04) on the supplemented diet than on the control diet. Water intake tended (P=0.06) to be higher onthe CSM+ diet than on the control diet, and was significantly at greater (P<0.01) high ambient temperaturethan at low temperature. The concentration of NH3-N in the rumen fluid (ranged from 310Â±17 to 413Â±20mg N/L) did not differ significantly either between diets or ambient temperatures. Blood plasma ureanitrogen concentration was significantly higher in sheep on the control diet than in those on thesupplemented diet, and at low than high temperature. The organic matter digestibility was not significantlyaffected by temperature and diet. The rate of live weight gain was significantly (P<0.01) reduced by highambient temperature and the interaction between diet and temperature was significant (P<0.01). At lowtemperature, lambs on the supplemented diet grew significantly faster than those on the control diet, butnot at high temperature. In conclusion, high ambient temperature increases respiration rate, rectaltemperature and water intake but reduces dry matter intake and live weight gain. Supplementation with100 g/d of cottonseed meal could not outweigh the depressing effects of constant high ambienttemperature and humidity imposed in this experiment.